2020
DOI: 10.1093/ntr/ntaa188
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of the Low Prevalence of Current Smokers Among COVID-19 Patients Hospitalized in Nonintensive Care Wards: Results From an Italian Multicenter Case–Control Study

Abstract: Introduction COVID-19, a respiratory illness due to SARS-CoV-2 coronavirus, was first described in December 2019 in Wuhan, rapidly evolving into a pandemic. Smoking increases the risk of respiratory infections; thus, cessation represents a huge opportunity for public health. However, there is scarce evidence about if and how smoking affects the risk of SARS-CoV-2 infection. Methods We performed an observational case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…While smoking was associated with hospitalization in crude analysis, it was not significant in multivariable analysis. Findings of previous studies of smoking and COVID-19 outcomes have been mixed, including increased, decreased, or no impact on risk as was found in this analysis [ 16 , 39 , 57 59 ]. Smoking has also been found to causes variable risk for SARS-CoV-2 infection suggesting a potential complex affect [ 60 ].…”
Section: Discussionmentioning
confidence: 46%
“…While smoking was associated with hospitalization in crude analysis, it was not significant in multivariable analysis. Findings of previous studies of smoking and COVID-19 outcomes have been mixed, including increased, decreased, or no impact on risk as was found in this analysis [ 16 , 39 , 57 59 ]. Smoking has also been found to causes variable risk for SARS-CoV-2 infection suggesting a potential complex affect [ 60 ].…”
Section: Discussionmentioning
confidence: 46%
“…Published meta-analyses reporting an unusually low pooled prevalence of smoking among hospitalized COVID-19 patients compared with population smoking rates ( Farsalinos et al, 2020 ; Farsalinos et al, 2020a ; Farsalinos et al, 2020b ) bolstered the debate about the connection between smoking and COVID-19. Other studies report that smokers are less likely to be diagnosed with or be hospitalized for COVID-19 ( Farsalinos et al, 2020a ; Farsalinos et al, 2020b ; Hippisley-Cox et al, 2020 ; Kowall et al, 2020 ; Giannouchos et al, 1101 ; Rossato et al, 2020 ; Meini et al, 2020 ; Simons et al, 2020 ), but, once hospitalized, they have higher odds for an adverse outcome ( Farsalinos et al, 2020b ; Alqahtani et al, 2020 ; Vardavas and Nikitara, 2020 ). Cox et al recently published a cohort study of 8.28 million participants, including 19,486 confirmed COVID-19 cases, and found that smoking was associated with lower odds for COVID-19 diagnosis and ICU admission ( Hippisley-Cox et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have reported this reduced risk of SARS-CoV-2 infection in active smokers in different contexts (cross-sectional studies in the general population; crosssectional, case-control or control studies in different populations). [17][18][19][20][21][22] Our results from a large multicenter prospective study in a young population of HCWs with 26.9% active smokers support the role of use of tobacco substances as protective against SARS-CoV-2 infection, which may act through the nicotine pathway. [23][24][25][26] This result should not encourage smoking to limit the risk of COVID-19; indeed, 78,000 deaths per year are due to smoking in France.…”
Section: Discussionmentioning
confidence: 61%